Targeting de novo lipogenesis and the Lands cycle induces ferroptosis in KRAS-mutant lung cancer - Caterina Bartolacci; Cristina Andreani; Gonçalo Vale; Stefano Berto; Margherita Melegari; Anna Colleen Crouch; Dodge L. Baluya; George Kemble; Kurt Hodges; Jacqueline Starrett; Katerina Politi; Sandra L. Starnes; et al. (Nature Communications, 2022)
Mutant KRAS (KM) is associated with poor prognosis in lung cancer and reported to promote lipid metabolism. Here, the authors show that fatty acid synthesis, which provides lipids to repair oxidized phospholipids through the FASN-Lands cycle axis, is a specific vulnerability for KM lung cancer.